Metode Bimbingan dan Konseling di Lembaga Pendidikan Islam Dalam Tafsir Al-Qur’an Pendekatan Tematik - Sarwan . (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2021)
Abstract This article discusses guidance and counselling methods in interpreting the al-Quran approach of maudhu'i (thematic). Based on the results of the analysis, it can be concluded that guidance and counselling is an activity of providing teaching and guidance to students, which can develop the potential for reason, psyche, faith and faith and can overcome problems in families, schools and communities properly and correctly independently based on Al-Qur'an and Al-Hadith. The correct foundation in carrying out the guidance and counselling process so that it can run well and produce positive changes for students regarding ways and paradigms of thinking, how to use potential conscience, how to feel, how to believe and how to behave through exemplary methods, habituation and giving advice (targhib-tarhib). Keyword : Methods, Guidance, Counseling, Al-Qur'an.